Path Profile Analysis of a LOS System Using 3-D Digital Map - AZIZ, Jabir S.; HAMADA, Saba T. (Nahrain University College of Engineering Journal, 2008)
Exponential growth of mobile communications, radio links and wireless networks has increased interest in many topics in radio propagation. Much effort is now devoted to refine radio propagation path-loss models for urban, suburban, and other environments together with substantiation by field data. Diffraction of a radio wave front occurs when the wave front encounters an obstacle that is large compared to the wavelength of the ray. The actual amount of obstruction loss is depended on the area of the beam obstructed in relation to the total frontal area of the energy propagated and to the diffraction properties of the obstruction. The objective for the system designer is to provide sufficient clearance of the obstacle without appreciable transmission loss due to the obstacle. The degree of intersection between the obstacle and the first Fresnel zone gives a good measure for obstruction loss. Remote sensing technologies (satellite images, aerial photography, and image processing) give attractive facilities which can be sacrifice to determine the topography differences and the path profile between any two points on the image of the area under test. Merging these facilities with the principle of wave propagation (First Fresnel Ellipsoid) represent the proposed idea of this paper. Data of path profile extracted from 3D remote sensing image by using ERDAS IMAGINE was used and analyzed by MATLAB tools to test the validity of any suggested path.